Experimental investigations on the productivity increase of solar stills utilising hybrid nanomaterials and water-cooling techniques - Ruchir Parikh; Shaival Parikh; Kamal Sharma; Ali Sohani; Vikrant P Katekar; Mushtaq Ahmad Ansari; L Natrayan; Mohd Asif Shah (Energy Exploration & Exploitation)
Solar stills are simple devices that can be used to remove salts from water. However, it has a lower distillate yield; hence, it is not popular. Increasing the solar energy collection at the absorber may help to address these issues. This is feasible by adopting highly absorbent energy storage substances. Hybrid nanomaterials have significant potential for this purpose, and they can boost the absorptivity of the absorber plate of solar stills. Taking this into account, a hybrid nanomaterial was synthesized in a laboratory and applied to the surface of a solar still absorber to achieve higher performance. Iron oxide (Fe 2 O 3 ) and copper oxide (Cu 2 O) nanoparticles were used in a 50:50 ratio. In addition, the current research employed a water sprinkler to enhance the condensation rate in the condensing region and consequently increase the distillation output of the solar still. A cooling water flow rate of 10 kg/h was used to sprinkle the condensing surface. According to the results, combining Fe 2 O 3 and Cu 2 O with epoxy resin increased the efficiency of the solar still by 34% when using a glass cooling approach and by 28% when operating without a glass cover cooling technique.